Alginate Microcapsules Loaded with Eryngium billardieri Extract and Its Application in Apple Juice - Seyed Amirsalar Abtahi; Zhaleh Khoshkhoo; Nasim Khorshidian; Mehrdad Mohammadi (Journal of Food Quality)
Fruit juices can be enriched with plant extracts to enhance the nutritional and biological value of the product. Plant extracts are rich sources of bioactive compounds such as polyphenols with potential health benefits for consumers. In the present study, alginate microcapsules containing Eryngium billardieri (EB) extract (derived from aerial parts) were prepared and incorporated into apple juice. EB extract as nonencapsulated (NE), encapsulated (E) in microcapsules, and the combination of nonencapsulated + encapsulated (NE + E) at different concentrations of 1, 3, and 5% (w/v) were added to apple juice. These sample groups were stored at 4°C, and quality characteristics were evaluated for 21 days with a week of regular intervals. The results showed that the prepared microcapsules were spherical shaped with a size of 150–170 μm. The highest (75.12%) and the lowest (70.63%) encapsulation efficiency (EE) on the first day of storage were obtained in microcapsules containing 5% and 1% extract, respectively. EE decreased during storage time, and the lowest EE (65.25%) was observed in samples with 1% extract on day 21. Incorporation of E and NE + E extract improved total anthocyanin, total phenolic content, total flavonoid content, and antioxidant activity of apple juice due to the protective effects of the encapsulation on polyphenol compounds in the extract. After 21 days of storage, the highest (10.21%) and the lowest (5.85%) ascorbic acid contents were observed in samples with 5% NE + E t and control samples, respectively. Addition of EB extract to apple juice prevented the growth of yeasts and molds till day 7, and encapsulation of extract could enhance inhibitory activity. In terms of sensory acceptability, apple juices containing encapsulated extract received higher scores by panelists as a result of masking the unpleasant color and flavor of the extract. These results indicate that the application of EB microcapsules has potential for use in the food industry.